ГЕНЕТИЧЕСКИЙ КОНТРОЛЬ ПУТЕЙ МОРФОГЕНЕЗА IN VITRO ИЗОГЕННЫХ ПО ГЕНАМ PPD ЛИНИЙ ОЗИМОЙ ПШЕНИЦЫ TRITICUM AESTIVUM L. (Experimental biology, 2017)
The features of the different ways of morphogenesis in vitro (callus formation, direct and indirect morphogenesis) isogenic lines for genes PPD winter wheat varieties Mironovskaya 808. The optimal conditionsfor the studied processes, showing their dependence on the type ofexplant, media composition and cultivation conditions. The differencesamong isogenic lines in the size of the cells of callus tissue, the rate of their formation, the manifestation of morphogenetic potential. It is shown that the ability of the genetic control of photoperiodic sensitivityof wheat in vivo determine thevarious ways of morphogenesis in vitr
Keywords: morphogenesis